Patogenisitas Cendawan Entomopatogen dari Rizosfir Kacang Tanah (Arachis hypogaea Linnaeus) terhadap Hama Penggerek Polong Etiella zinckenella Treitschke (Lepidoptera: Pyralidae) - Reflinaldon, Reflinaldon; Martinius, Martinius (Jurnal Proteksi Tanaman (Journal of Plant Protection), 2017)
The objective of this study was to get entomopathogenic fungi isolates of bean plant rhizosphere derived from Nagari Sawah Tangah, District Pariangan, Tanah Datar Regency and to determine their pathogenicity on pod borer E. zinckenella. Isolation method was performed by diluting the soil samples in a serial dilution into 10-3 and cultured in PDA media. Furthermore, the purification was based on the shape and color of the fungus colonies. A total of 16 isolates obtained at the initial stage were selected by testing them against the fifth instar larvae Tenebrio molitor. Results showed that only 4 isolates (STA 1, STA 2.2, STA 5, and STB 3.1) could be further tested against E. zinckenella pod borer using completely randomized design (CRD). The highest pathogenicity isolates was exhibited by STA 1 belonged to Metarhizium genera.